Hubungan Beban Kerja dengan Kualitas Pelayanan pada Perawat Pelaksana di Ruang IGD RSUD Dr. Doris Sylvanus Palangka Raya - Yeni Kristina Dewi; Takesi Arisandy; Nia Pristina (Pusat Riset dan Inovasi Nasional, 2025)
The Emergency Department (ED) is the first destination for patients in emergency situations. One of the key healthcare providers in delivering services to patients is the nurse. The quality of hospital services is partly influenced by the workload of nurses. This condition can trigger work-related stress, necessitating research to determine whether there is a relationship between workload and service quality among nursing staff in the ED of RSUD dr. Doris Sylvanus Palangka Raya. This study aims to identify the relationship between workload and service quality among nursing staff in the ED of RSUD dr. Doris Sylvanus Palangka Raya. Method: This correlational study employed a cross-sectional approach to examine the relationship between workload and service quality among 40 nursing staff members, using total sampling and Chi-Square test. Data were collected using a workload questionnaire and a service quality questionnaire. Results: The Chi-Square test analysis yielded a p-value = 0.028, indicating a significance level of p < 0.05. Therefore, H1 was accepted, showing a significant relationship between workload and service quality, with a substantial degree of association. Conclusion: The study demonstrates a significant relationship between workload and service quality among nursing staff in the ED of RSUD dr. Doris Sylvanus Palangka Raya.